On the inhomogeneous hydration kinetics and stiffness evolution of HNBR‐MgO reactive elastomer composites. Issue 22 (5th February 2016) - Qu, Meng; Lou, Yucun; Han, Dingzhi; Gewily, Ahmed Amr; Robisson, Agathe
ABSTRACT: Swellable elastomers are widely used in oilfield industry for sealing and zonal isolation applications. These materials need to sustain a large amount of external load after swelling. A newly developed reactive hydrogenated nitrile butadiene rubber (HNBR) based elastomer composite with magnesium oxide (MgO) as filler can swell and stiffen when exposed to water, which makes it ideal for oil field applications. However, both the filler hydration and the stiffness evolution inside this composite material are observed to be highly inhomogeneous even for samples on the length scale of millimeters. To understand this coupled diffusion‐hydration process is critical for applications of these materials with larger length scales. In this work, the hydration kinetics and stiffness evolution of the HNBR‐MgO composite are quantitatively studied on microscopic level. The extent of MgO hydration along the thickness of the sample are measured at the different stage of swelling. These results are used to determine the diffusion coefficient of water inside the composite. The diffusivity increases orders of magnitude after the filler hydration. In addition, the modulus change is non‐proportional to the degree of filler hydration as demonstrated by instrumented grid indentation on the hydrated composites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43420. Abstract :